An Efficient Petasis Boronic–Mannich Reaction of Chiral Lactol Derivatives Prepared from d-Araboascorbic Acid - Mandai, Hiroki; Yamada, Hiroshi; Shimowaki, Keita; Mitsudo, Koichi; Suga, Seiji (Synthesis, 2014)
Optically active polyhydroxy trans-1,2-amino alcohols were efficiently synthesized in good to excellent yields by the Petasis boronic–Mannich reaction of an amine, an organoboronic acid, and a chiral lactol, which was prepared from d-araboascorbic acid or its diastereomer. Further transformations of the resulting Petasis products were investigated in detail to obtain chiral building blocks containing three continuous stereogenic centers.
Keywords: asymmetric synthesis; chiral pool; coupling; diastereoselectivity; domino reaction; lactones